"Hood Sign" in Nuclear Medicine: An Unusual Presentation of Mantle Cell Lymphoma as Detected on FDG PET/CT. (16th December 2022) - Prakash, Anjali; Purandare, Nilendu; Shah, Sneha; Agrawal, Archi; Puranik, Ameya; Rangarajan, Venkatesh
Abstract: Mantle cell lymphoma is a rare and aggressive non-Hodgkin lymphoma with a high propensity for extranodal involvement, typically seen in the liver, marrow, and gastrointestinal system. Being an FDG-avid disease and a sensitive modality for detecting both nodal and extranodal disease, FDG PET/CT is recommended in the workup of mantle cell lymphoma. We present a rare pattern of cutaneous involvement of the head-neck region in a patient with mantle cell lymphoma, which can be described on FDG PET/CT as a "hood sign."